Chronic rhinosinusitis with nasal polyps: Key considerations in the multidisciplinary team approach - Oliver Pfaar; Anju T. Peters; Camille Taillé; Thijs Teeling; Jared Silver; Robert Chan; Peter W. Hellings (Clinical and Translational Allergy, 2025)
Abstract Background Chronic rhinosinusitis with nasal polyps (CRSwNP) is a recurrent inflammatory disease associated with several comorbidities and a significant disease burden for patients. Treatments include corticosteroids and sinonasal surgery, but these can be associated with the risk of adverse events and nasal polyp recurrence. Biologic treatments such as mepolizumab can be used as an add‐on treatment and are effective at reducing surgery and corticosteroid use. Main text Patients with CRSwNP may be seen by a specialist in one of several different areas and often experience delayed diagnosis due to the need to see multiple physicians, as well as misdiagnosis resulting from lack of sufficient expertise within any one speciality. Multidisciplinary team (MDT) approaches have been shown to be effective in optimising the treatment and clinical management of other respiratory diseases, such as aspirin‐exacerbated respiratory disease and severe asthma. In CRSwNP, an MDT approach may reduce diagnostic delays, mitigate secondary disease burden, and reduce overprescription of corticosteroids and antibiotics. Conclusion This article provides an overview of the patient perspective of MDTs, existing approaches and barriers to adoption, lessons learnt from allied and rare diseases, how to address under‐recognised aspects of CRSwNP, and other key considerations for developing an MDT approach.